A super-agonist of growth hormone-releasing hormone causes rapid improvement of nutritional status in patients with chronic kidney disease - Niemczyk, Stanisław; Sikorska, Hanna; Więcek, Andrzej; Żukowska-Szczechowska, Ewa; Załęcka, Klaudia; Gorczyńska, Joanna; Kubik, Małgorzata; Czerwieńska, Beata; Gosek, Katarzyna; Veldhuis, Johannes D.; Wagner, David A.; Gaudreau, Pierrette; et al. (Kidney international, 2010)
Chronic kidney disease is frequently associated with protein-energy wasting related to chronic inflammation and a resistance to anabolic hormones such as insulin and growth hormone (GH). In this study, we determined whether a new GH-releasing hormone super-agonist (AKL-0707) improved the anabolism and nutritional status of nondialyzed patients with stage 4-5 chronic kidney disease randomized to twice daily injections of the super-agonist or placebo. After 28 days, this treatment significantly increased 24-h GH secretion by almost 400%, without altering the frequency or rhythmicity of secretory bursts or fractional pulsatile GH release, and doubled the serum insulin-like growth factor-1 level. There was a significant change in the Subjective Global Assessment from ‘mildly to moderately malnourished’ to ‘well-nourished’ in 6 of 9 patients receiving AKL-0707 but in none of 10 placebo-treated patients. By dual-energy X-ray absorptiometry, both the mean fat-free mass and the body mineral content increased, but fat mass decreased, all significantly. In the AKL-0707-treated group, both serum urea and normalized protein equivalent of nitrogen appearance significantly decreased with no change in dietary protein intake, indicating a protein anabolic effect of treatment. Thus, our study shows that stimulation of endogenous GH secretion by AKL-0707 overcomes uremic catabolism of patients with advanced chronic kidney disease.